Journalistic identity and audience perceptions: paradigm and models under construction in the African Great Lakes region - Frère, Marie-Soleil (Brazilian journalism research, 2015)
This article is based on a research conducted in three African countries (Burundi, Rwanda and the Democratic Republic of the Congo), focusing on the recent evolution of the journalistic profession and the way journalists are perceived today and represented by members of the audience polled in five localities of the region. In the last twenty years, journalism has been deeply transformed, following the liberalization of the media sector, on one hand, and the murderous civil wars which marked the three countries on the other hand. New formats and new roles have appeared for the media, as well as new professional standards for journalists (codes of ethics, regulations from regulatory authorities, journalists education and training curricula, professional associations), often encouraged by foreign donors and international NGOs. This paper aims at showing that, behind these changes, a new « journalistic paradigm » has taken shape, a consequence of both internal dynamics within the profession and external assignments (imposed by the State and the evolution of the market), and also of new demands emanating from the public. In an unstable political, economic and security context, the changes of the journalistic paradigm have transfigured media content, as well as the perception by the local public of the role that journalists have to play in society, and of what the citizens may expect from them, in a region where democracy is still widely under construction.